Waste separation behavior in costa rican homes (Dissertare, 2019)
The discussion about human activity and how it affs the environment has become a relevant topic. There is much evidence of the irresponsible way in which waste is managed. Sewers and spaces converted into garbage dumps are sources of disease and flooding. Given this problem, this quantitative, explanatory and field research aimed to determine the factors that explain the behavior of separation or recycling of waste in Costa Rican homes, for which purpose data from the National Survey of Households of the year 2016, using a binary logistic regression model, whose dependent variable was represented by the aforementioned waste separation behavior, modeled as a dichotomous variable, with the answer “Yes” or “No”. In the set of predictive variables, aspects inherent to the head of the household were considered, first of all: which include: gender, level of education, employment status and marital status (accompanied or not by couple). On the other hand, the homes’ own characteristics were incorporated: located in an urban or rural area, its net income and Internet access. All the variables, except the working condition of the head of the household, were significant and showed a positive effect on the disposition to separate waste. The feature with the greatest impact on this provision is the location of the home in a rural area. Therefore, it is necessary to articulate public policies that stimulate the separation of waste in urban areas, considering that they host the highest percentage of the country's population.
Keywords: waste separation; recoverable waste; homes; recycling